Developing a national undergraduate standardized curriculum for future healthcare professionals on "Making Every Contact Count" for chronic disease prevention in the Republic of Ireland. Issue 4 (3rd July 2020) - Sinclair, Dawn; Savage, Eileen; O' Brien, Maria; O'Reilly, Anthony; Mullaney, Carmel; Killeen, Marie; O'Reilly, Orlaith; Field, Catherine Anne; Fitzpatrick, Patricia; Murrin, Celine; Connolly, Deirdre; Patterson, Aileen; et al.
ABSTRACT: This report describes the development of the first national undergraduate interprofessional standardized curriculum in chronic disease prevention for healthcare professionals in the Republic of Ireland. This project brought together for the first time all higher education institutions nationwide in a novel collaboration with the national health service i.e. the Health Service Executive (HSE), to develop a standardized national curriculum for undergraduate health care professions. The curriculum sits within the framework of Making Every Contact Count, the goal of which is to re-orientate health services to embed the ethos of prevention through lifestyle behavior change as part of the routine care of health professionals. The core focus of Making Every Contact Count is chronic disease prevention, targeting four main lifestyle risk factors for chronic disease; tobacco use, alcohol consumption, physical inactivity and unhealthy eating. Making Every Contact Count is a key component of Healthy Ireland, the Irish national framework for health and wellbeing. The aim of the curriculum is to prepare newly qualified health professionals with the skills needed to support patients to achieve lifestyle behavior change delivered as part of routine clinical care.